The coastal refraction-diffraction wave propagation model - Dat, Nguyen Tien; Manh, Dinh Van; Son, Nguyen Minh (Vietnam Journal of Mechanics, 1995)
A mathematical model on linear wave propagation toward shore is chosen and corresponding software is built. The wave transformation outside and inside the surf zone is considered including the diffraction effect. The model is tested by laboratory and field data and gave reasonables results.